AnemiaAR: um Serious Game para apoio ao ensino da hematologia - Bianchi, Isabela (2021)
Serious games can be useful educational support tools for different areas of knowledge, such as Medicine. These applications, combined with technologies like Mixed Reality, provide a differentiated experience that can increase the engagement of students and teachers. In this context, this work aims to present the development of AnemiaAR, a Mixed Reality Serious Game to support the teaching of Hematology, useful to help students and teachers in the visualization and presentation of anemia concepts. This application evaluated preliminary the sample considering the use of a sociodemographic questionnaire, a questionnaire based on the Technology Acceptance Model, and two modules of the Game Experience Questionnaire. Fourteen medical students from the University of Passo Fundo participated in the pilot study. The preliminary results were satisfactory, showing good acceptance and positive experience of the game, besides improvements. The study also pointed out differences in the evaluation of the game between participants, considering the prior experience in games, the previously attend the Hematology course, and the time spent to perform the game tasks.